Effects of interleukin 17A (IL-17A) neutralization on murine hepatitis virus (MHV-A59) infection - Aparicio, Jose Luis (2017)
Mice infected with mouse hepatitis virus A59 (MHV-A59) develop hepatitis and autoantibodies (autoAb) to liver and kidney fumarylacetoacetate hydrolase (FAH), a fact closely related to the release of alarmins such as uric acid and/or high-mobility group box protein 1 (HMGB1). We studied the effect of neutralizing monoclonal antibodies (MAb) against IL-17A in our model of mouse MHV-A59-infection. MAb anti IL-17F and anti-IFNγ were used to complement the study. Results showed that transaminase levels markedly decreased in MHV-A59-infected mice treated with MAb anti-IL-17A whereas plasmatic Ig concentration sharply increased. Conversely, MAb anti-IL-17F enhanced transaminase liberation and did not affect Ig levels.Serum IFNγ was detected in mice infected with MHV-A59, and its concentration increased after MAb anti-IL-17A administration. Besides, MAb anti-IFNγ greatly augmented transaminase plasmatic levels. IL-17A neutralization did not affect MHV-A59-induction of HMGB1 liberation and slightly augmented plasmatic uric acid concentration. However, mice treated with the MAb failed to produce autoAb to FAH. The above results suggest a reciprocal regulation of Th1 and Th17 cells acting on the different MHV-A59 effects. In addition, it is proposed that IL-17A is involved in alarmins adjuvant effects leading to autoAb expression.